A novel surface molecularly imprinted polymer as the solid-phase extraction adsorbent for the selective determination of ampicillin sodium in milk and blood samples - Ningli Wu; Zhimin Luo; Yanhui Ge; Pengqi Guo; Kangli Du; Weili Tang; Wei Du; Aiguo Zeng; Chun Chang; Qiang Fu (Elsevier, 2016)
Surface molecularly imprinted polymers (SMIPs) for selective adsorption of ampicillin sodium were synthesized using surface molecular imprinting technique with silica gel as a support. The physical and morphological characteristics of the polymers were investigated by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), elemental analysis and nitrogen adsorption-desorption test. The obtained results showed that the SMIPs displayed great adsorption capacity (13.5 μg/mg), high recognition ability (the imprinted factor is 3.2) and good binding kinetics for ampicillin sodium. Finally, as solid phase extraction adsorbents, the SMIPs coupled with HPLC method were validated and applied for the enrichment, purification and determination of ampicillin sodium in real milk and blood samples. The averages of spiked accuracy ranged from 92.1% to 107.6%. The relative standard deviations of intra- and inter-day precisions were less than 4.6%. This study provides a new and promising method for enriching, extracting and determining ampicillin sodium in complex biological samples.